Birth during the moderate weather seasons is associated with early onset of type 1 diabetes in the Mediterranean area. Issue 7 (19th April 2020) - Adar, Adi; Shalitin, Shlomit; Eyal, Ori; Loewenthal, Neta; Pinhas‐Hamiel, Orit; Zuckerman Levin, Nehama; Dally‐Gottfried, Orna; Landau, Zohar; Zung, Amnon; Levy‐Khademi, Floris; Zangen, David; Tenenbaum‐Rakover, Yardena; et al.
Abstract: Aim: To assess the association of seasonal and perinatal parameters with early age of type 1 diabetes (T1D) onset. Methods: A cross‐sectional review of all medical records of T1D patients born between the years 1990 and 2005, and diagnosed before/by the age of 10 years, from 13 university‐affiliated paediatric medical centres in Israel, was performed. Data included: gender, ethnicity, seasons of birth and disease onset, birth gestational age and weight, and autoimmune diseases of the probands and their first‐degree family members. Statistical analysis included the Chi‐square test or Mann‐Whitney test, as appropriate and multivariate regression analysis. Results: Enrolled were 1571 T1D patients at a median age of T1D onset 6.9 years (IQR 4.4, 8.4); 336 of them presented before 4 years of age. The median age of this group was 2.5 years (IQR 1.7, 3.2), and of the 1235 patients who presented after 4 years of age, median presentation age was 7.5 years (IQR 6.1, 8.8). Multivariate regression analysis demonstrated that a more recent birth year; OR = 1.06, 95% CI 1.02‐1.1, P = 0.003, and birth during the moderate weather months (September, October, March, and April) were significantly associated with younger age at T1D onset; OR = 1.68, 95% CI 1.17‐2.4, P = 0.005. Conclusions: Our novel finding demonstrates the association between younger than 4 years old age at presentation and birth during moderate weather months. The results also support previous reports, that there is a slight increase in the annual incidence of T1D in the youngest age groups.